2004
DOI: 10.1055/s-2004-815815
|View full text |Cite
|
Sign up to set email alerts
|

Überprüfung der Gültigkeit und Zuverlässigkeit des deutschen Female Sexual Function Index (FSFI-d)

Abstract: ZusammenfassungHintergrund: Weibliche Sexualstörungen haben eine hohe Prä-valenz in der Bevölkerung. Trotzdem erfahren sie weit weniger Aufmerksamkeit als männliche Störungen. Ein Grund kann der Mangel an validierten diagnostischen Instrumenten im deutschsprachigen Raum sein. Der FSFI ist ein einfaches 19-Item-Selbstbeurteilungs-Instrument, das in den USA entwickelt wurde. Bisher ist es validiert für Frauen mit Erregungsstörungen, Libidoproblemen und Orgasmusstörungen. Wir führten eine Überset-zung und Adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(19 citation statements)
references
References 0 publications
0
16
0
3
Order By: Relevance
“…Sexual functioning was examined using the German version of the Female Sexual Function Index (FSFI; Rosen et al, 2000) validated by Berner et al (2004). The FSFI is a multidimensional self-report instrument and is considered to be the gold standard for the assessment of female sexual functioning.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual functioning was examined using the German version of the Female Sexual Function Index (FSFI; Rosen et al, 2000) validated by Berner et al (2004). The FSFI is a multidimensional self-report instrument and is considered to be the gold standard for the assessment of female sexual functioning.…”
Section: Methodsmentioning
confidence: 99%
“…According to Wiegel et al (2005), women with and without sexual dysfunction can be discriminated by a total FSFI cutoff value of 26.55. Regarding the psychometric properties of the German version of the FSFI, Berner et al (2004) reported satisfactory results in their validation study, with internal consistencies for the FSFI domains and total score ranging from α = 0.75 (satisfaction) to α = 0.95 (pain). In the present study, we found an excellent internal consistency for the total FSFI score (Cronbach’s alpha = 0.92) and a range from α = 0.74 (satisfaction) to α = 0.91 (pain) for the FSFI domains.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Knowledge About Pelvic Organ Prolapse Questionnaire, validated for German- and Russian-speaking patients, was used to assess level of knowledge about POP (score 0–16) [11]. Sexually active patients were asked to complete the Female Sexual Function Index (FSFI) questionnaire written in their respective language [12, 13].…”
Section: Methodsmentioning
confidence: 99%
“…As far as the primary objective is concerned, vita sexualis was assessed using the Female Sexual Function Index (FSFI-d), a validated 19-item questionnaire for the assessment of female sexual dysfunction. This questionnaire has been validated for the use in German speaking countries [11]. The primary endpoint was assessed by intrapersonal paired comparison, preoperative versus 12 months postoperative, Secondary objectives included the assessment of pain (FSFI-d pain sub score), pelvic floor function (German version of pelvic floor questionnaire, PFQ) [12], patient satisfaction, recurrence, mesh exposure and safety.…”
Section: Methodsmentioning
confidence: 99%